Production of succinic acid from sugarcane molasses supplemented with a mixture of corn steep liquor powder and peanut meal as nitrogen sources by Actinobacillus succinogenes. (1st June 2015) - Shen, N.; Qin, Y.; Wang, Q.; Liao, S.; Zhu, J.; Zhu, Q.; Mi, H.; Adhikari, B.; Wei, Y.; Huang, R.
Abstract: The potential of using corn steep liquor powder (CSLP), peanut meal (PM), soybean meal (SM), cotton meal (CM) and urea as the substitute of yeast extract (YE) as the nitrogen source was investigated for producing succinic acid (SA). Actinobacillus succinogenes GXAS137 was used as the fermenting bacterium and sugarcane molasses was used as the main substrate. None of these materials were able to produce SA as high as YE did. The CSLP could still be considered as a feasible and inexpensive alternate for YE as the yield of SA produced using CSLP was second only to the yield of SA obtained by YE. The use of CSLP‐PM mixed formulation (CSLP to PM ratio = 2·6) as nitrogen source produced SA up to 59·2 g l −1 with a productivity of 1·2 g l −1 h −1 . A batch fermentation using a stirred bioreactor produced up to 60·7 g l −1 of SA at the same formulation. Fed‐batch fermentation that minimized the substrate inhibition produced 64·7 g l −1 SA. These results suggest that sugarcane molasses supplemented with a mixture of CSLP and PM as the nitrogen source could be used to produce SA more economically using A. succinogenes . Significance and Impact of the Study: Succinic acid (SA) is commonly used as a platform chemical to produce a number of high value derivatives. Yeast extract (YE) is used as a nitrogen source to produce SA. The high cost of YE is currently the limiting factor for industrial production of SA. This study reports the use of a mixture of corn steep liquor powder (CSLP) and peanut meal (PM) as an inexpensive nitrogen source to substitute YE. The results showed that this CSLP‐PM mixed formulation can be used as an effective and economic nitrogen source for the production of SA.